Critical Factors Influencing the Acceptance and Usage of Electronic Medical Records System in Malaysian Public Hospitals Based on A Multi-Criteria Perspective Analysis - Odai Mohammad Ahmad Enaizan (Universiti Sains Islam Malaysia, 2024)
Matric: 4130140(FST)